PERSEPSI GURU PAMONG TERHADAPKETERAMPILAN MENGELOLA KELASGURU PRAKTIK PENGALAMAN LAPANGAN INSTITUT AGAMA ISLAM SAMBAS ANGKATAN 2019 DI SDS TARBIYATUL ISLAM - Haliza Nur Putri; Eliyah Eliyah; Sera Yuliantini (CV. ADIBA AISHA AMIRA, 2024)
This thesis discusses the Perceptions of Civil Service Teachers on Class Management Skills of Practical Field Experience Teachers at the Sambas Islamic Institute Class of 2019 at SDS Tarbiyatul Islam. This research has two objectives, namely: 1) Describe the skills of the 2019 IAIS Sambas Field Experience Practice teachers in managing classes at SDS Tarbiyatul Islam. 2) Describe the teacher's perception of the skills of the 2019 IAIS Sambas Field Experience Practice teachers in managing classes at SDS Tarbiyatul Islam. This research uses a qualitative approach and a phenomenological type of research. Data collection techniques use interviews and documentation. The data analysis technique uses data reduction, presenting data and drawing conclusions. The data validity checking technique uses triangulation and member checking. The research results show that: 1. The skills of the 2019 IAIS Sambas Field Experience Practical teacher in managing the class apply the principles of class management (warm and enthusiastic, challenge, variety, flexibility and self- discipline), use an approach to class management, use an approach according to the learning conditions faced, organize study room by paying attention to (seating arrangements, arrangement of teaching tools, arrangement of beauty and cleanliness of the classroom, ventilation and lighting). When controlling learning conditions, PPL teachers try to create conducive learning conditions in several ways (showing responsiveness, dividing attention, giving clear instructions, reprimanding and providing reinforcement, modifying behavior and solving behavior that causes problems). 2. The teacher's perception of the IAIS Sambas Field Experience Practice teacher's skills in managing the classroom has shown good results because they have implemented the principles of classroom management, apart from that the teacher has also been free to use the classroom management approach, organize the learning space and control learning conditions properly. Good.